Advance visual information, awareness, and anticipation skill - Jackson, R. C.; Mogan, P. (Journal of Motor Behavior, 2007)
The authors examined 13 skilled, 13 recreational, and 11 novice players' awareness of the advance visual information that they used to judge tennis serve direction. Participants viewed video clips of serve actions under 5 conditions of spatial occlusion. The authors assessed participants' awareness by comparing the different groups' confidence associated with correct and incorrect judgments and by conducting a postexperiment free-recall test. The results indicated that information from the ball toss and the arm + racquet region underpinned players' anticipation skill and that greater expertise was accompained by increasing awareness of the information on which judgments were based. The authors discuss the implications of the present results for researchers' use of confidence ratings to assess awareness in perceptual-judgment tasks.